2018
DOI: 10.4236/jbbs.2018.84012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Aluminum Administration on Affective and Cognitive Behavior in Male and Female Rats

Abstract: In this study, we investigated the effect of chronic exposure of low doses of Aluminum on affective and cognitive disorders in male and female rats. Twenty-five rats for each gender are used and the treatment carried out for 8 weeks. Animals received distilled water for control or an intraperitoneal injection of different doses of Aluminum: 0.125, 0.25, 0.5 and 1 mg/kg. Behavioral performance is measured in various tests mainly the Open Field, Elevated Plus Maze, Force Swimming Test, Morris Water Maze, Y-maze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 25 publications
6
11
0
1
Order By: Relevance
“…Our results showed that AlCl3 (in ADM group) impaired short term working memory, where spontaneous alternation behaviour (SAP) was reduced. This result supported with Xing et al (2018) and Zghari et al (2018) found that exposure of rat and mice to Al or AlCl3 and D-galactose reduced spontaneous alternation percentage in Y-maze test. While treatment with GS and MO enhanced the reduced SAP and this were in agreement with Kim et al (2017) and Omotoso et al (2018) who reported that red ginseng and ginsenoside moringa olifera increased alternation percent in Y-maze.…”
Section: Discussionsupporting
confidence: 84%
“…Our results showed that AlCl3 (in ADM group) impaired short term working memory, where spontaneous alternation behaviour (SAP) was reduced. This result supported with Xing et al (2018) and Zghari et al (2018) found that exposure of rat and mice to Al or AlCl3 and D-galactose reduced spontaneous alternation percentage in Y-maze test. While treatment with GS and MO enhanced the reduced SAP and this were in agreement with Kim et al (2017) and Omotoso et al (2018) who reported that red ginseng and ginsenoside moringa olifera increased alternation percent in Y-maze.…”
Section: Discussionsupporting
confidence: 84%
“…A dose of 1 mg/kg CuCl 2 showed maximum anxiety-like and depression-like symptoms as compared to controls. The Cu effects observed in our study are similar to numerous heavy metals (Cd, Al and Ni)[7] [8][10].…”
supporting
confidence: 81%
“…Exposure to metals from environment, which are highly neurotoxic and have no other biological functions, such as aluminum (Al), lead (Pb) and cadmium (Cd), has long been debated as a potential environmental risk factor for mood disorders [7] [8]. However, nowadays, people are mainly focusing on biologically important metals such as copper (Cu), because their imbalance is related to a profound physiological alteration including the central nervous system (CNS) [9] [10].…”
Section: Introductionmentioning
confidence: 99%
“…The comportmental studies showed that chronic and sub chronic exposure to Aluminum causes an increased immobility time of rats in the forced swimming test; reflecting the depressed state of animal. This state is due to the reduction of serotonin level in central serotoninergic system [30], in cortex [9], hippocampus, striatum, and spinal cord brain regions of rat pups following oral exposure to Al 31 .…”
Section: Discussionmentioning
confidence: 99%